2017
DOI: 10.1002/eji.201747132
|View full text |Cite
|
Sign up to set email alerts
|

The role of the miR‐148/‐152 family in physiology and disease

Abstract: MicroRNAs (miRNAs) are endogenously encoded ∼22 nt small non-coding RNAs. They function as key players of many cellular processes by base pairing with target mRNAs and thereby impairing gene expression at the post-transcriptional level. Recent findings demonstrate a critical role of many miRNAs in immune cell differentiation and immune responses, which is also associated with the development and progression of many tumor and non-tumor diseases. Here we review the multifaceted miRNA-148/-152 family members cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 134 publications
3
71
1
Order By: Relevance
“…Consistent with our finding, tumor suppressive functions of miR-148a-3p have been demonstrated in many cancer types (35,37), including colorectal cancer (36,41). Indeed, miR-148a-3p has been reported to be downregulated in tumors, compared with their normal counterpart, which often correlated with advanced stage, where miR-148a-3p silencing was caused by DNA hypermethylation of its promotor (35,37,42). Decreased levels of miR-148a-3p were associated with poor clinical outcomes in a variety of cancers (43)(44)(45).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our finding, tumor suppressive functions of miR-148a-3p have been demonstrated in many cancer types (35,37), including colorectal cancer (36,41). Indeed, miR-148a-3p has been reported to be downregulated in tumors, compared with their normal counterpart, which often correlated with advanced stage, where miR-148a-3p silencing was caused by DNA hypermethylation of its promotor (35,37,42). Decreased levels of miR-148a-3p were associated with poor clinical outcomes in a variety of cancers (43)(44)(45).…”
Section: Discussionsupporting
confidence: 93%
“…Recent reports have suggested that miR-148a-3p can work as a tumor suppressive miRNA that is frequently downregulated in colorectal cancer and other malignancies (35)(36)(37). To confirm the tumor suppressive function of miR-148a-3p in vitro, we used exogenous overexpression by transfecting miR-148a-3p mimic using a colorectal cancer cell line, HCT116 (Fig.…”
Section: Mir-148a-3p As a Tumor Suppressor In Colorectal Cancermentioning
confidence: 99%
“…Again, miR‐148a is the most expressed milk microRNA, and it is consistently reported in all milk small RNA sequencing, supporting its evolutionary importance in lactation and possibly for the newborn's development and health (Friedrich et al., ; Zempleni et al., ). Moreover, the sequences of human and bovine miR‐148a are identical.…”
Section: Micrornas Found In Milk From Other Speciesmentioning
confidence: 81%
“…In the human genome, the miR-148-family consists of 3 members that are located in different chromosomal regions: miR-148a is at 7p15.2, miR-148b is at 12q13.13 and miR-152 is at 17q21.32. 27,28 The mature sequences of the guide strands of these miRNAs are similar and the seed sequences (UCAGUGCA) are identical. 29 Most analyses have focused on guide strands of the miR-148-family in normal physiological conditions or in cancer cells.…”
Section: Discussionmentioning
confidence: 99%